Early Detection of Cerebral Infarction With Middle Cerebral Artery Occlusion With Functional Near-Infrared Spectroscopy: A Pilot Study - Kwon, Hyuksool; Kim, Kyuseok; Jo, You Hwan; Park, Min Ji; Ko, Sang-Bae; Kim, Tae Jung; Kang, Jihoon; Bae, Hyeon-Min; Lee, Ji Eun (Frontiers in Neurology, 2018)
Background: NIRSIT, a functional near-infrared spectroscopy (fNIRS) device with 204 channels, can measure oxyhemoglobin (HbO2) and deoxyhemoglobin (HbR) in nonpulsatile blood flow noninvasively using the absorption difference between HbO2 and HbR at a wavelength of 700-1000 nm and can display the perfusion status in real time. Objective: We applied NIRSIT to patients with stroke to evaluate the usefulness of NIRSIT as an fNIRS device for the early detection of stroke. Methods: We performed a prospective pilot study in an emergency department. Adult patients who had suspected symptoms and signs of stroke within 12 hours of the first abnormal time and who underwent intravenous thrombolysis or intra-arterial thrombectomy with acute middle cerebral artery (MCA) or internal carotid artery (ICA) infarction were enrolled. NIRSIT was applied to the patients before the imaging study, and the perfusion status of the brain was displayed in real time at the bedside. We compared the NIRSIT results with the mean transit time (MTT) map from perfusion computed tomography (PCT) and the time-to-peak (TTP) map from perfusion-weighted magnetic resonance imaging (PWI). Results: Six male and 3 female patients were enrolled, and the median age was 74 years. The most common symptom was unilateral extremity weakness (77.8%), followed by dysarthria (33.3%) and aphasia (11.1%). The median National Institutes of Health Stroke Scale (NIHSS) score was 17. All cases of MCA infarction showed different cerebral oxygen saturation values between bilateral lobes of the brain in fNIRS imaging, and these values matched the PCT and PWI results. Conclusions: The brain hemisphere with low oxygen saturation on fNIRS showed hypoperfusion on PCT or PWI. The fNIRS device could be useful in assessing the perfusion status of the brain and detecting MCA or ICA infarction in real time at the bedside.